Genotype-phenotype correlation in hypertrophic cardiomyopathy: moving towards precision medicine?. (19th May 2022) - Porretta, AP; Nana Davies, S; Maurizi, N; Frochaux, A; Pruvot, E; Monney, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Hypertrophic cardiomyopathy (HCM) is the most prevalent inherited cardiomyopathy. In spite of approximately 50 mutations causally associated to HCM, pathogenic variants in the thick-filament genes, encoding myosin 7 (MYH7) and cardiac myosin-binding protein C (MYBPC3), are responsible for up to 50% of clinically diagnosed HCM cases and for about 80% of patients (pts) with a confirmed genetic aetiology. However, the complex model of inheritance, encompassing genetic modifiers and environmental causes, accounts for the typical incomplete penetrance and variable expressivity, and still hampers genotype-phenotype correlation. Purpose: We present a series of pts clinically diagnosed with HCM at our tertiary university center and enrolled in the Institutional Prospective Registry of HCM (IPRHCM). We report the clinical presentation and outcome, according to specific genotype. Methods: Based on clinical criteria for HCM, 65 consecutive pts (42 ± 17 years) were enrolled in the IPRHCM. The diagnosis was made after a cardiac assessment including, among others, echocardiography and cardiac stress test (CST). Among them, 28 pts (43%) underwent a genetic test. A genetic variant was detected in 23 patients (82%) including 11 MYBPC3 (48%), 10 MYH7 (43%), 1 MYL3 (4%) and 1 TNNI3 (4%) variants. According to genotypes, we divided pts into two groups: the MYH7 group (10/23 pts) and the non-MYH7 one (13/23 pts). Of note, no pathogenic variant was detected among the 5 remaining pts (18%). Results: No significant difference was observed in age at diagnosis and gender distribution between the MYH7 and the non-MYH7 group. On standard ECG, the MYH7 group had a significant lower basal heart rate (60 ±3 vs 73 ±3 bpm, p=0.01) and a trend (p =0.09) towards a more frequent occurrence of left bundle branch block (30% vs 0%). Of note, no significant difference was observed between groups in terms of medical therapy (i.e., betablockers). Despite similar LV outflow tract pressure gradient (LVOTPG) at rest, MYH7 pts had a significantly higher LVOTPG during Valsalva manoeuvre (12 [9-80] vs 7 [7-8] mmHg, p=0.03) and a trend (p =0.08) towards a greater left atrium diameter (44 ±2 vs 39 ±2 mm). At CST, MYH7 pts had significant lower peak systolic blood pressure (149±10 vs 185 ±8 mmHg, p=0.01). We finally appreciated a significant difference between groups in term of outcome. MYH7 pts underwent more often septal myectomy (70% vs 55%, p =0.02) and showed a trend (p =0.07) towards a more frequent occurrence of heart failure or heart transplantation (30% vs 0%) as compared to non-MYH7 pts. Conclusions: Our study supports the findings of a more severe phenotype with a worse prognosis in MYH7 pts than that of other CMH genotypes, as suggested by greater LVOTPG during Valsalva manoeuvre, greater left atrial enlargement, abnormal exercise pressure response and by a more frequent occurrence of septal myectomy and of heart failure/transplantation.